The Allure and Peril of Genetics Exceptionalism: Do We Need Special Genetics Legislation? - Sonia M. Suter (Washington University Law Quarterly, 2001)
This Article asserts that genetic information is not unique and that concerns about abuses of information should not be limited to genetic information, but should extend to other medical information. Not only is genetic information like other medical information, but treating the two differently under the law leads to unintended inequities between individuals and classes, which raises serious questions about the propriety of public policy based on genetics exceptionalism.
Keywords: Genetic screening; Right of privacy; Discrimination; Legislation; Equal protection; Genetic discrimination; Human genetics